Curriculum That is Not Yet Independent - Situmorang, Bonar (Journal of Sumatera Sociological Indicators, 2023)
The "kurikulum merdeka" and â€œasesmen nasionalâ€ are part of the "merdeka belajar" policy that has been gradually implemented since 2020. In terms of implementation, the readiness of regions and schools varies, as experienced in the Mentawai Islands Regency. The author is interested in examining the reality and challenges of implementing this policy. The focus of this article is, first, to describe the potential of education starting from schools, students, teacher competencies, and the allocation of education budgets. Second, to describe the results of the implementation of the "Merdeka Curriculum" and the national assessment in all elementary schools in the Mentawai Islands Regency. The method used is a literature review, with secondary data sourced from journals, books, regional education reports, and the county's educational reports. The results found are as follows: 40 elementary school students have dropped out, out of 1,322 elementary school educators, only 19.1% are certified, and 80.9% are not certified. Teachers with qualifications appropriate for their roles make up 89.4%, while those not meeting the qualifications account for 10.6%. In 2022, the county government allocated a budget of Rp 716.6 billion from the APBD for the education sector. The readiness level for the implementation of the "Merdeka Curriculum" includes 97 schools that are â€œmandiri belajar,â€ 16 schools that have â€œmandiri berubahâ€, and no schools currently â€œmandiri berbagi.â€ The student literacy achievement is the lowest in the entire Sumatera Barat region, ranking 17th out of 19 cities/counties in Sumatera Barat for numeracy achievement, while student character development achievement is still at an early stage. These conditions indicate that education and the curriculum in the Mentawai Islands Regency are not fully independent.